Micro Health Project - Khadka, Ajay; Sharma, S; Regmi, S; Chapagain, S; Lamichhane, B; Baral, S; Thapa, P; KC, Ankur; Thapa, A; Mandal, B; Khadka, P; Poudel, A; et al. (Journal of Gandaki Medical College-Nepal, 2017)
Community health diagnosis is a comprehensive assessment of health status of the community in relation to its social, physical and biological environment. The purpose of community health diagnosis is to define existing problems, determine available resources and set priorities for planning, implementing and evaluating health action, by and for the community. The community health diagnosis program began on 4th September 2015 and continued till 13th September 2015 in ward no 1 and 5 Rupakot VDC, Kaski, Nepal. The program was organized in following phases: data collection, data analysis, first community presentation, prioritization of need and planning of micro health project (MHP), implementation and evaluation of MHP, and final community presentation. On the basis of the observed and the felt needs of the community, we found the real needs and prioritized them as follows. For community: Proper water purification, information about common diseases, KAP on diseases, knowledge on TB and DOTS. For school-going children: Education on environmental sanitation, education on personal hygiene - teeth brushing and hand washing, adolescent health education. We launched micro health project (MHP) on these topics, conducting school-based as well as community-based programs. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, Page: 59-62